Legal Protection for Notaries in the Backdoor Listing Process Based on Capital Market Law in Indonesia (Study of PT Pantai Indah Kapuk Dua Tbk) - Ranti, Viani Chrisanta; Adam, Richard (Journal of Law, Politic and Humanities, 2024)
Notaries as defined by Law Number 30 of 2004 amended by Law Number 2 of 2014 are public officials authorized to create authentic deeds and play a critical role in capital market transactions. In Indonesia, the capital market is governed by Law Number 8 of 1995, which serves businesses to raise funds, with Initial Public Offerings (IPOs) being a common method. However, due to the high cost and lengthy process through IPOs, companies often seek faster and more cost-effective alternatives such as backdoor listings. The backdoor listing process involves a company becoming public by acquiring an already listed company without undergoing the IPO process. This study uses a normative legal research method to analyze primary and secondary legal materials to provide a comprehensive understanding of this topic. Despite its cost efficiency compared to traditional IPOs, backdoor listings still have legal uncertainties. Notaries, who are crucial in this process, require legal protection to ensure compliance and professionalism. This highlights the need for specific regulations governing the backdoor listing process. Ensuring the legal protection of notaries is essential for maintaining the integrity of capital market transactions and providing a secure environment for all parties involved.